Illustrated Tales From Shakespeare - Lamb, Charles and Lamb, Mary (Kibworth Books, 1999)
This book is a modern adaptation of Shakespearean Tales by The Charles and Mary Lamb Classic. It contains tales like The Tempest, A Midsummer Night's Dream and many more.
Keywords: Drama; English, Irish, Scottish, Welsh; European; Shakespeare